Bacterial Diversity and Composition in the Internal Organs of Taiga Bean Goose, Greater White-Fronted Goose and Willow Ptarmigan as a New Tools in the Arctic Biomonitoring System - Evdokia Durnova; Elena Karmanova; Tatiana Sorokina; Ksenia Mayorova; Andrey Aksenov (Diversity)
Birds, fish, and marine mammals consumed by indigenous people are included in Arctic biomonitoring. However, there are still many gaps in the data on the microbiota associated with these animals. In the current study, we used high-throughput 16S rRNA gene sequencing to explore the bacterial diversity and composition in the intestines of willow ptarmigans, greater white-fronted geese, and taiga bean geese, which are widely consumed by indigenous people in the Arctic. For the first time, meta-taxonomic data have been obtained on the lungs of wild resident and migratory birds of the Russian North. The potentially pathogenic bacterial genera Helicobacter and Olsenella were found in the intestinal microbiomes of three bird species and in the lungs of willow ptarmigan. Bacteria of the genus Staphylococcus were individually identified in the intestines of willow ptarmigan, Campylobacter sp. in the intestines of taiga bean goose, and Sutterella sp. in the intestines of greater white-fronted goose as potential pathogens. The primary findings will be used to propose a next-generation sequencing scheme for monitoring both chemical and biological contaminants in the Arctic in line with One Health approach.